Pengaruh Penambahan Kulit Jeruk Lemon (Citrus limon) pada Pemanfaatan Serbuk Batang Singkong sebagai Obat Nyamuk Bakar - Puspita, Ratna; Asmara, Sandi; Rahmawati, Winda; Kuncoro, Sapto (Jurnal Agricultural Biosystem Engineering, 2022)
The abundant amount of cassava stem waste in Indonesia has not been utilized optimally. As an effort to optimize the utilization of cassava stem waste, it is used as a raw material for mosquito coils with the addition of active ingredients as insect repellents. One of the natural insect repellents is lemon peel which contains limonoids as an active substance. In the making processing of mosquito coils, adhesives are also needed. so that the composition of waste cassava stems, lemon peel, and adhesive affects the characteristics of mosquito coils. Important parameters that were observed to obtain the characteristics of mosquito coils were shatter resistance index, moisture content, density, burn duration, smoke distribution, and organoleptic tests.  Result of research of P1 showing until P5 have an effect on burn duration. Weight one mosquito coils at various treatment gyrate 11,39-17,04 and old burn 7,1 hour - 8 hour Keyword: Burn Duration, Lemon Peel, Mosquito Coils.